A quasi-Newton interior point algorithm applied to constrained optimum design in computational fluid dynamics - Herskovits, Jose; Laporte, Emmanuel; Tallec, Patrick Le; Santos, Gines (European Journal of Computational Mechanics, 1996)
This paper introduces and describes a second order interior point method well adapted to. constrained shape optimal design in engineering. The· theoritical background is presented and detailed implementation procedures are given in the case of nonlinear inequality constraints. The algorithm is then applied to two significative shape optimum problems in Computational Fluid dynamics.